The role of circulating cytokines in heart failure: a bidirectional, two-sample Mendelian randomization study - Zheng, Haoran; Mao, Xinxin; Fu, Zhenyue; Chen, Chunmei; Lv, Jiayu; Wang, Yajiao; Wang, Yuxin; Wu, Huaqin; Li, Yvmeng; Tan, Yong; Gao, Xiya; Zhao, Lu; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Cytokines play a pivotal role in the progression of heart failure (HF) by modulating inflammatory responses, promoting vasoconstriction, and facilitating endothelial injury. However, it is now difficult to distinguish the causal relationship between HF and cytokines in observational studies. Mendelian randomization (MR) analyses of cytokines probably could enhance our comprehension to the underlying biological processes of HF.Methods: This study was to explore the correlation between 41 cytokines with HF at the genetic level by MR analysis. We selected a HF dataset from the Heart Failure Molecular Epidemiology for Therapeutic Targets (HERMES) 2018 and a cytokine dataset from a meta-analysis of cytokine levels in Finns. Two-sample, bidirectional MR analyses were performed using Inverse Variance Weighted (IVW), Weighted Median and MR-egger, and the results were tested for heterogeneity and pleiotropy, followed by sensitivity analysis.Results: Genetic prediction of high levels of circulating Macrophage inflammatory pro-tein-1β(MIP-1β) (P=0.0389), Interferon gamma induced protein 10(IP-10) (P=0.0029), and Regu-lated on activation, normal T cell expressed and secreted(RANTES) (P=0.0120) expression was associated with an elevated risk of HF. HF was associated with the increased levels of circulating Interleukin-2 receptor, alpha subunit(IL-2ra) (P=0.0296), Beta nerve growth fac-tor(β-NGF) (P=0.0446), Interleukin-17(IL-17) (P=0.0360), Basic fibroblast growth factor(FGF-basic) (P=0.0220), Platelet derived growth factor BB(PDGF-BB) (P=0.0466), and Interferon-gamma(IFN-γ) (P=0.0222); and with decreased levels of Eotaxin (P=0.0133). The heterogeneity and pleiotropy of the cytokines were acceptable, except for minor heterogeneity of FGF-basic and IL-17.These findings provide compelling evidence for a genetically predictive relationship between cytokines and HF, emphasizing a great potential of targeted modulation of cytokines in 2 slowing the progression of HF. This study draws further conclusions at the genetic level, providing a basis for future large-scale clinical trials.